Utilization, knowledge and attitudes concerning sealants among Malaysian dentists: a national survey - Razak, I.A.; Esa, R.; Jalallundin, R.L.; Jaafar, N. (1990)
The aim of this postal survey was to assess the utilization, knowledge and attitude concerning sealants among Malaysian dentists. A pretested questionnaire was sent to all dentists (1217) who were on the Dentist Register of Malaysia of 1987. A response rate of 61.1% was obtained. The results indicate that 52.6% of the respondents have used sealants, but of these only 13.6% have used them frequently. The two "knowledge" related questions receiving the most support concerned the suitability of the first permanent molars for sealants and the loss of sealants attributable to problems at the time of application. The two "attitudinal" questions receiving the most support concerned the value of sealants in preventing dental caries and the need for the profession to expand more efforts toward increasing public demand for sealants. Only about 50% of the respondents believed that sealants are cost-effective.